Pengaruh Air Rebusan Daun Binahong Terhadap Penyembuhan Luka Perineum pada Ibu Nifas di TPMB Susiani, Amd. Keb Banyuwangi Tahun - Putriani Putriani; Erik Toga; Erlin Novitasari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Perineal wounds are tears that occur during childbirth, either spontaneously or through assisted delivery. If not properly treated, they can lead to infections. The healing time varies depending on hygiene and the mother's health condition. Perineal wound healing can be facilitated through non-pharmacological treatments, including binahong leaves. The binahong plant has antibacterial, antioxidant, and anti-inflammatory properties, making it potentially effective in accelerating perineal wound healing. This study aims to determine the effect of boiled binahong leaf water on perineal wound healing in postpartum mothers at Susiani, Amd. Keb Independent Midwife Practice Banyuwangi in 2024. The research was conducted at TPMB Susiani, Amd. Keb Banyuwangi, Gang Lombok Perum Villa Asri I Block A-6 Sukowidi, Klatak Village, Kalipuro District, Banyuwangi Regency, from May to June 2024. This study evaluated the effect of boiled binahong leaf water on perineal wound healing using a quasi-experimental design with a posttest-only control group. Of 40 postpartum mothers, 20 received binahong leaf treatment, while 20 did not. The sampling technique used was consecutive sampling. The boiled binahong leaf water was administered for five days, twice daily in the morning and evening. Data analysis was performed using the Wilcoxon test with SPSS. Ethical approval number: 179/01/KEPK-STIKESBWI/V/2024. The results showed that after the intervention, nearly all respondents experienced a reduced wound severity by day 5, with perineal wounds showing signs of healing. The Wilcoxon test yielded an Asymp. Sig. (2-tailed) value of 0.000, indicating a significant effect of this therapy, with 60% of mothers in the intervention group experiencing good wound healing. The data indicate an impact on perineal wound healing in postpartum mothers at Susiani, Amd. Keb Independent Midwife Practice Banyuwangi in 2024. Binahong leaves can serve as a complementary alternative for postpartum mothers with perineal tears.